CRIMINOLOGY CHARACTERISTICS AND PREVENTION OF SUICIDE AMONG MILITARY SERVANTS - Karelin, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
Suicide is a phenomenon inherent in both developed countries and countries with a low socio-economic standard of living. The causes of all suicides are mostly socio-psychological in nature. That is why, in our opinion, it is necessary to start investigating suicide from the understanding of a person's mental state, his inner worldview, and not from the act of suicide. Suicide has no age. The key factors leading to suicide are considered psychological, since suicide is a psychological phenomenon. The rest of the factors act indirectly, through the emotional experiences and motivation of a person. According to the official data of the World Health Organization, reflected in the mass media, annually in the world more than 800,000 people take their own lives, which means that every 40 seconds at least one person commits suicide, another two million people make unsuccessful attempts kill yourself. In general, in the modern world, suicide is one of the most common causes of death, second only to death due to aging, serious diseases and external causes (road accidents, accidents, intentional homicides and bodily injuries, etc.). Since the Armed Forces of Ukraine are an integral part of society and that is why, especially during hostilities, general negative processes and influences also affect their personnel. Therefore, it should be noted that the problems of suicidal behaviour, unfortunately, are also relevant for the Armed Forces of Ukraine. The interaction of several risk factors "leads to suicide, among which is a crisis situation that, due to individual characteristics, a veteran (fighter) cannot cope with on his own. Sometimes the decision to die is a response to a hopeless situation: the impossibility of changing it, although it changes a person psychologically, and even physically (injury, etc.). The loss of a "significant object" (for example, a sibling) can "trigger" depression, suicidal moods and actions. During the period of experiencing and overcoming a difficult crisis, military personnel and veterans need psychological support and, if necessary, inpatient treatment. No less important is the support of relatives and friends, as well as the whole society. In war, everything is simple – there is an enemy, there is you, and behind you are native Ukrainian lands, millions of people. You clearly know your tasks and responsibilities. After returning from the front, soldiers are faced at all levels with indifference, misunderstanding, disrespect, and sometimes rude attitude, which leaves scars in their wounded souls and hearts. Resentment, anger, misunderstanding and indifference of the environment, constant pain in the soul and body takes over the mind and the moment comes when everything, even life, has no meaning.
Keywords: suicide, military personnel, Armed Forces of Ukraine, criminological characteristics, prevention, war, veterans